Odpowiedź :
2x - 3(x+5) =< 4(x+5)
2x-3x-15 =< 4x+20
-2x+3x+4x >=-20-15
5x >= -35
x >= -7
_________________________________
|/////////////////////////////
------|------------------------------------------->
-7
2x-3x-15 =< 4x+20
-2x+3x+4x >=-20-15
5x >= -35
x >= -7
_________________________________
|/////////////////////////////
------|------------------------------------------->
-7
2x-3(x+5)≤4(x+5)
2x-3x-15≤4x+20
-x-4x≤15+20
-5x≤35/:(-5)
x≥-7
Uwaga : nastąpiła zmiana zanku nierówności gdyż dzielono przez liczbę ujemną
2x-3x-15≤4x+20
-x-4x≤15+20
-5x≤35/:(-5)
x≥-7
Uwaga : nastąpiła zmiana zanku nierówności gdyż dzielono przez liczbę ujemną
2x*3(x+5)<4(x+5)
2x*3x+5<4x+5
2x*3x-4x<-5+5
2X>0
--------------2---------1----------0---------->
--------------/
2x*3x+5<4x+5
2x*3x-4x<-5+5
2X>0
--------------2---------1----------0---------->
--------------/